Critical Literacy Model On Students In Preparing Final Assignments To Avoid Plagiarism - Hayati, Kinanti Resmi; Zawawi, Zawawi; Sholihatin, Endang (International Journal for Educational and Vocational Studies, 2020)
The aim of this study is to develop a Critical Literacy model for Management Economics department’s Students of economics and business faculty of UPN "Veteran" Jawa Timur in Arranging Final Project to Avoid Plagiarism. The research method uses a qualitative and quantitative approach which is applied research with case studies. The research’s location is in Management Economics department’s Students of economics and business faculty of UPN "Veteran" Jawa Timur. The data sources are students, lecturers and administrative staff in Management Economics department. Primary data are questionnaire results and data from interviews. Secondary data are from documents, observation data, and media. The implementation of data collection in the field is regulated through the following strategies, (a) the determination of informants by purposive sampling (for key informants) and snow ball for informant development, (b) interviewing informants, (c) taking notes, (d) asking descriptive and structural question, 5) conducting interview analysis, (e) making domain analysis, (f) finding themes according to the research problem, (g) surveying to students. The research checks the data validity by using data source triangulation techniques. The research conclusions are formulated a critical literacy model that can be applied by economics management study program Management Economics department’s students in preparing Final Project to avoid plagiarism; 1) students prepare topics; 2) students look for references that are relevant to the topic; 3) students start to compile scientific papers (Final assignment) with the correct paraphrasing, quotation, and citation/bibliography techniques; 4) check plagiarism; 5) Similarity tolerance with maximum of 30%; and 6) Final assignment avoids plagiarism.